2013
DOI: 10.1016/j.contraception.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Fertility goal-based counseling increases contraceptive implant and IUD use in HIV-discordant couples in Rwanda and Zambia

Abstract: Background HIV discordant heterosexual couples are faced with the dual challenge of preventing sexual HIV transmission and unplanned pregnancies with the attendant risk of perinatal HIV transmission. Our aim was to examine uptake of two long-acting reversible contraceptive (LARC) methods – intrauterine devices (IUDs) and hormonal implants – among HIV discordant couples in Rwanda and Zambia. Study Design Women were interviewed alone or with their partner during routine cohort study follow-up visits to ascerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 32 publications
3
38
1
Order By: Relevance
“…Comparable to other findings by our group indicating that HIV status was not predictive of LARC uptake in multivariate analyses [36], we did not see a role for HIV status in method downgrading or upgrading behaviors in this study. Similarly, a study among HIV positive and negative couples in Malawi found that, while HIV positive individuals were more likely to desire to cease childbearing relative to HIV negative individuals, HIV positivity did not translate into higher contraception uptake [37].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Comparable to other findings by our group indicating that HIV status was not predictive of LARC uptake in multivariate analyses [36], we did not see a role for HIV status in method downgrading or upgrading behaviors in this study. Similarly, a study among HIV positive and negative couples in Malawi found that, while HIV positive individuals were more likely to desire to cease childbearing relative to HIV negative individuals, HIV positivity did not translate into higher contraception uptake [37].…”
Section: Discussioncontrasting
confidence: 63%
“…Prior evaluation by our group noted that among discordant couples condoms were systematically used more often among the LARC users as compared to those using only condoms [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 4 respondents were initially concerned that LARC may decrease condom use in HIV discordant couples, though in fact condom use is more consistent among LARC-using discordant couples in Rwanda compared with non-LARC using discordant couples. 29 Several participants cited antenatal clinics as an optimal venue to discuss HIV testing and FP because husband and wife attend together for CVCT. Stakeholders gave insights around the need for preser-vice as well as in-service training for both FP and HIV counseling and testing services.…”
Section: Discussionmentioning
confidence: 99%
“…Recall bias may have also affected responses of individual questionnaires. We did not assess clients' experiences of the quality of family planning services, which can impact LARC uptake 25 . Nonetheless, the lack of active LARC providers and heavy work burden described in the questionnaires were consistent with the focus group discussions.…”
Section: Discussionmentioning
confidence: 99%